SIGNIFICANCE OF CA15-3 IN CARCINOMA OF THE BREAST WITH VISCERAL METASTASES - Bhunisha; Haider, Ghulam; Shaikh, Zoya; Memon, Paras; Shahid, Aisha; Rahul, Raja; Kumar, Pavan; Beg, Shumyla; Parkash, Jai (Journal of Ayub Medical College Abbottabad, 2024)
Background: The most common malignancy and second most common cause of death is breast cancer among women. About 2.09 million fatalities from breast cancer happened in 2018. The objective was to evaluate the elevated CA15-3 in breast cancer patients with visceral metastases presenting at the tertiary care hospital of Karachi. Methods: It was a cross-sectional study conducted at the Department of Oncology of Jinnah Postgraduate Medical Center from 15th December 2018 to 15th November 2019. Female patients aged 26-80 years diagnosed with visceral metastatic (defined as metastasis to lung, liver, brain and adrenal glands) breast cancer were included in the study. The diagnosis of breast cancer was confirmed on histopathology whereas the metastatic sites were evaluated using physical examination and imaging. The serum CA15-3 concentration was assessed using assay kits. The serum CA15-3 level of 0-32 U/ml was taken as normal range for all the patients whereas CA15-3 level greater than 32 U/L was considered as elevated CA15-3. SPSS version 23 was used to enter and analyze data. Results: A total of 139 females were included in the study. The mean age & BMI of the patients were reported as 46.5 years & 26.69 kg/m2. In the majority of the patients' metastases were detected in the liver (n=54), 92 in the lungs+ parenchymal disease, 20 in adrenal glands, 12 in pleural effusion and 10 in the brain. Out of 139 patients with visceral metastases, 52(37.4%) had normal CA15-3 level whereas 87 (62.6%) had elevated serum CA15-3 levels (>32 U/L). Conclusion: The serum CA15-3 tumour marker is elevated significantly in visceral metastases and can be used as a prognostic marker in metastatic breast cancer patients.